Design and development of a portable resistive sensor based on α‐MnO2/GQD nanocomposites for trace quantification of Pb(II) in water. Issue 5 (23rd March 2021) - Gupta, Amit K.; Khanna, Mansi; Roy, Souradeep; Pankaj,; Nagabooshanam, Shalini; Kumar, Ranjit; Wadhwa, Shikha; Mathur, Ashish
Abstract: The occurrence of heavy metal ions in food chain is appearing to be a major problem for mankind. The traces of heavy metals, especially Pb(II) ions present in water bodies remains undetected, untreated, and it remains in the food cycle causing serious health hazards for human and livestock. The consumption of Pb(II) ions may lead to serious medical complications including multiple organ failure which can be fatal. The conventional methods of heavy metal detection are costly, time‐consuming and require laboratory space. There is an immediate need to develop a cost‐effective and portable sensing system which can easily be used by the common man without any technical knowhow. A portable resistive device with miniaturized electronics is developed with microfluidic well and α‐MnO2 /GQD nanocomposites as a sensing material for the sensitive detection of Pb(II). α‐MnO2 /GQD nanocomposites which can be easily integrated with the miniaturized electronics for real‐time on‐field applications. The proposed sensor exhibited a tremendous potential to be integrated with conventional water purification appliances (household and commercial) to give an indication of safety index for the drinking water. The developed portable sensor required low sample volume (200 µL) and was assessed within the Pb(II) concentration range of 0.001 nM to 1 uM. The Limit of Detection (LoD) and sensitivity was calculated to be 0.81 nM and 1.05 kΩ/nM/mm 2, and was validated with the commercial impedance analyser. The shelf‐life of the portable sensor was found to be ∼45 days.